In idiopathic scoliosis distances of spinal cord to thoracic pedicle are within 2 mm in a large region of the thoracic apex - Joost A. Burger; Luis Becker; Zhao Li; Zhen Wang; Hendrik Schmidt; Matthias Pumberger; Friederike Schömig (Scientific Reports, 2024)
Abstract Despite a 15% misplacement rate of screws in idiopathic scoliosis surgery, little is known about the relationship between pedicles and nerve structures in the entire thoracic curve. This study aimed to explore the spinal cord’s proximity to the pedicle wall at each thoracic vertebra in the entire thoracic curve, while considering different anatomical changes. Spinal cord to medial pedicle distances were measured on magnetic resonance imaging in 73 patients who underwent posterior spinal fusion with pedicle screw instrumentation. Associations with different variables were examined. A total of 51 patients (69.9%) showed a distance within 2 mm at the apex vertebra on the concave side, more than 50% had a distance within 2 mm in the next thoracic vertebra level above and below, and more than 25% two levels above and below. Weak correlations were found between proximity of the spinal cord at the apex vertebra and vertebra’s level and Cobb angle on the concave side (r = − 0.310, P = 0.008, r = 0.380, P = 0.001, respectively). These results emphasize the importance of thorough assessment when placing thoracic pedicle screws in idiopathic scoliosis patients. Further research is warranted to develop surgical strategies aimed at preventing potentially neurological complications resulting from screw misplacement.